2018
DOI: 10.1002/adem.201800551
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Ablation Behaviors of ZrB2–SiC Composites Sintered with Nano‐Sized Particles

Abstract: Ultra-high temperature ceramic (UHTC) is one of the most promising materials used in thermal protection system for hypersonic flight vehicles. In this work, ZrB 2 -0.5 vol% SiC composites are fabricated with nano-sized ZrB 2 and SiC particles by spark plasma sintering (SPS) at 1500 C. The average density of the composites reaches 5.47 g cm À3 , while the average grain size is only 1 μm. Then, single and cyclic ablation tests are conducted using a plasma generator. Ablation mechanisms and microstructure evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Some studies confirmed that cyclic ablation rates were lower than those under single loading when the total impacting time of combustion was the same, because the longer single loading time resulted in higher surface temperatures [ 29 , 30 , 31 ]. Other studies [ 32 , 33 ] suggested that shorter single loading times resulted in higher cyclic ablation rates for the strengthened thermal shock. Recently, cyclic ablation of C/C-SiC-ZrC-ZrB 2 under different loading spectra indicated that the ablation rates rose sharply as the single loading time increased from ms to s [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies confirmed that cyclic ablation rates were lower than those under single loading when the total impacting time of combustion was the same, because the longer single loading time resulted in higher surface temperatures [ 29 , 30 , 31 ]. Other studies [ 32 , 33 ] suggested that shorter single loading times resulted in higher cyclic ablation rates for the strengthened thermal shock. Recently, cyclic ablation of C/C-SiC-ZrC-ZrB 2 under different loading spectra indicated that the ablation rates rose sharply as the single loading time increased from ms to s [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enormous research has been carried out to study the effect of reinforcements on the mechanical, oxidation, and thermal performance of ZrB 2 . SiC‐reinforced ZrB 2 composites have received special interest, [ 23–25 ] considered as baseline UHTC composites [ 17,26–29 ] with 20 vol% SiC as optimal for aerospace applications; [ 30–33 ] however, studies regarding the effect of reinforcement on tribological behavior are available in scarce as compared with studies on other aspects, such as mechanical, thermal, and oxidation behavior.…”
Section: Introductionmentioning
confidence: 99%